Solve sin x-3 sin 2x + sin 3x = COS X - 3 cos 2x + cos3x
Answers
Answered by
3
Answer:
sinx - 3sin2x + sin3x = cosx - 3cos2x + cos3x
sinx + sin3x - 3sin2x = cosx + cos3x - 3cos2x
2sin2xcosx - 3 sin2x - 2cos2x cosx + 3cos2x = 0
sin2x(2cosx - 3) - cos2x(2cosx - 3) = 0
(2cosx - 3)(sin2x - cos2x) = 0
sin2x = cos2x as cos x ≠ 3/2
2x = 2n∏ ± (∏/2 - 2x)
x = n∏/2 + ∏/8
Similar questions
English,
4 months ago
Biology,
4 months ago
Biology,
4 months ago
Math,
8 months ago
Environmental Sciences,
8 months ago
Computer Science,
1 year ago
Biology,
1 year ago
Hindi,
1 year ago